2015
DOI: 10.1038/ejhg.2015.104
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study to explore how professionals in the United Kingdom make decisions to test children for a sickle cell carrier status

Abstract: European guidelines recommend that, unless there are clear benefits of autosomal recessive carrier testing in childhood, it should be deferred to protect children's autonomous decision making. Although it is believed that children receive testing in the United Kingdom, it is unclear how or why professionals make decisions to provide tests. Semi-structured interviews were conducted with 25 professionals in the United Kingdom who advise about, and undertake, childhood sickle cell trait testing. Data were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…HCPs were then more willing to grant the test because they were more confident that parents had evaluated the pros and cons of testing. This concurs with findings from previous research (Noke et al 2015).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…HCPs were then more willing to grant the test because they were more confident that parents had evaluated the pros and cons of testing. This concurs with findings from previous research (Noke et al 2015).…”
Section: Discussionsupporting
confidence: 94%
“…An assessment of best interest was challenging, as it was often difficult to separate out the best interests of an individual child and her/his family and identify who was best placed to decide. This finding adds weight to similar conclusions in two recently published studies which focussed on carrier testing (Noke et al 2015;Vears et al 2015). We concentrated more broadly on predictive testing showing that this is an issue for HCPs for a range of tests.…”
Section: Discussionsupporting
confidence: 82%
“…Concerning the analysis of the qualitative collection found, we adopted the thematic analysis technique adapted by Gomes 23 , based on the principles of Bardin 25 . The central concept of this analysis is the theme that "comprises a bundle of relationships and can be graphically presented through a word, sentence or summary" 23 (p.86).…”
Section: Methodsmentioning
confidence: 99%
“…1,[13][14][15][16][17][18][19] Studies reporting carrier-testing practices of health professionals indicate that genetic health professionals are willing to facilitate carrier testing for autosomal recessive and X-linked conditions in unaffected children to varying degrees. [13][14][15][16]20 For example, in an interview-based study of 17 key informant genetic health professionals in Australia, we found that all our participants initially recommended against carrier testing in children following parental requests, with some preemptively discussing it as a test they generally do not perform. 13 However, although some participants said they never facilitate carrier testing in children younger than age 16 years, others allow parents who persist with their request to have their child tested.…”
Section: Introductionmentioning
confidence: 99%
“…13 This is in contrast to a recent United Kingdom-based study in which 16 of the 25 health professionals interviewed (64%) recommended that parents have carrier testing performed in older siblings following the diagnosis of a child with sickle cell disease, with only 6 discouraging testing. 20 Although there has been some exploration of parents' perspectives on receiving carrier results as an incidental finding from newborn screening, [21][22][23] few studies have explored parents' perspectives on carrier testing for their other children following the diagnosis of an affected child. 1,[17][18][19] Although existing studies provide further evidence that some unaffected siblings receive carrier testing, little research has explored parents' experiences with the request-to-test process, the impact of knowing a child's carrier status, and whether parents communicate carrier information to their children.…”
Section: Introductionmentioning
confidence: 99%